Agricultural employment and the economy in 2000 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Although agriculture is the major occupation and employer of most ACP countries. As the figures above show, its contribution to the gross domestic production (the value of everything produced within a country) can be small. In part, this is because...